What pace for direct electrification? Insights from co-optimised pathways in the European chemical and power sector - Clément Cabot; Manuel Villavicencio (Energy Conversion and Management: X, 2025)
Decision makers and private investors impacted by the evolution of the carbon price should limit risks associated with investments in decarbonised options, notably for electrified options. This research demonstrates that considering only static future power prices and carbon content might be insufficient when accelerated sectoral electrification effort is foreseen. To illustrate the phenomenon, this research focuses on the conditions and the extent of electrification in decarbonising the chemical sector in Central-West Europe. Specifically, energy transition pathways until 2050 are considered for the power and the chemical sectors using a novel co-optimisation model, minimising the net present cost of both sectors and considering different carbon price scenarios and deployment rates. The findings indicate that not accounting for the power sector constraints when assessing the chemical sector’s transition pathways overestimates greenhouse gas (GHG) reduction potential and underestimates the net present cost by 3% in some scenarios. The results hold in scenarios considering carbon capture technologies. Overall, this research highlights the importance of upstream power sector investments in evaluating preferred pathways for GHG reduction in downstream sectors. Potential welfare losses are found in the case of transition pace asymmetry between the two sectors or resulting from imperfect anticipation of the respective decarbonisation trajectory of each sector.